VIDEO PEMBELAJARAN COOPERATIVE LEARNING UNTUK TENAGA PENGAJAR - Yudho Setyo Nugroho; I Nyoman Sudana Degeng; Sihkabuden Sihkabuden (Graduate School of Universitas Negeri Malang, 2017)
The purpose of this research is producing and to examine the feasibility of instructional video cooperative learning for teachers elementary school. The model used is a model development Borg & Gall with ten steps. The product development is validated by expert of material 1 and 2 with the level of validity 92,5% and 87,5%, by expert of media 1 and 2 with the level of validity 98% and 95%, by aspect of attractiveness with a level of validity 90%, aspect of implementation NHT with a level of validity 94% means the instructors are able to implement it, aspect of implementation TPS with a level of validity 96% means the instructors are able to implement it, aspect of implementation TTW with a level of validity 95% means the instructors are able to implement it, aspect of implementation TSTS with a level of validity 95% means the instructors are able to implement it, aspect of effectiveness NHT model get the percentage of 72% might be said that it is effective, aspect of effectiveness TPS model get the percentage of 83% might be said that it is effective, aspect of effectiveness TTW model get the percentage of 86% might be said that it is effective, aspect of effectiveness NHT model get the percentage of 83% might be said that it is effective.Tujuan penelitian adalah untuk menghasilkan dan menguji kelayakan video pembelajaran cooperative learning untuk guru sekolah dasar. Model pengembangan yang digunakan adalah model Borg & Gall dengan sepuluh langkah. Pengembangan produk ini divalidasi oleh ahli materi 1 dengan tingkat kevalidan 92,5%, ahli materi 2 dengan tingkat kevalidan 87,5, ahli media 1 dengan tingkat kevalidan 98%, ahli media 2 dengan tingkat kevalidan 90%, uji coba kemudahan dengan tingkat kevalidan 95%, uji coba kemenarikan dengan tingkat kevalidan 90%, uji coba pelaksanaan model NHT dengan tingkat kevalidan 94% dengan kualifikasi guru mampu melaksanakan, uji coba pelaksanaan model TPS dengan tingkat kevalidan 96% dengan kualifikasi guru mampu melaksanakan, uji coba pelaksanaan model TTW dengan tingkat kevalidan 95% dengan kualifikasi guru mampu melaksanakan, uji coba pelaksanaan model TSTS dengan tingkat kevalidan 95% dengan kualifikasi guru mampu melaksanakan, uji coba keefektifan model NHT memperoleh persentase 72% sehingga dikatakan efektif, uji coba keefektifan model TPS memperoleh persentase 83% sehingga dikatakan efektif, uji coba keefektifan model TTW memperoleh persentase 86% sehingga dikatakan efektif, dan uji coba keefektifan model TSTS memperoleh persentase 83% sehingga dikatakan efektif.